2021
DOI: 10.1021/acs.jafc.1c01755
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Properties of Recombinant Ligase Butelase-1 and Its Application in Cyclizing Food-Derived Angiotensin I-Converting Enzyme Inhibitory Peptides

Abstract: Butelase-1 is an efficient ligase from Clitoria ternatea with wide applications in the food and biopharmaceutical fields. This research aimed to achieve high-efficiency expression of butelase-1 and explore its application in food-derived angiotensin I-converting enzyme (ACE) inhibitory peptides. The recombinant butelase-1 zymogen was prepared at a yield of 100 mg/L in Escherichia coli and successfully activated at pH 4.5, resulting in a 6973.8 U/L yield of activated butelase-1 with a specific activity of 348.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 49 publications
(133 reference statements)
0
12
0
Order By: Relevance
“…Our previous studies have shown that recombinant butelase 1 exhibited maximum cyclization activity at 45 °C . Here, the cyclization reaction was performed at 40 °C to alleviate the effect of heating on the activity of AMPs.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Our previous studies have shown that recombinant butelase 1 exhibited maximum cyclization activity at 45 °C . Here, the cyclization reaction was performed at 40 °C to alleviate the effect of heating on the activity of AMPs.…”
Section: Resultsmentioning
confidence: 99%
“…Butelase 1 was prepared according to our previous report with a brief modification. 23 In brief, the recombinant vector pMAL-c6t-butelase 1 was transformed into the E. coli cell. The cells were grown in LB medium at 37 °C until the absorbance of culture reached 0.4−0.6 at 600 nm, and then, 0.1 mM isopropyl β-D-thiogalactoside was added to the culture for inducing target protein.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recombinant PAL proenzymes can be expressed in bacteria, but the expressed proteins are often present as misfolded proteins in inclusion bodies (Nguyen et al, 2014) and the yield of soluble proteins is fairly low (Tang & Luk, 2021). Although incorporation of large fusion tags such as MBP can increase the yield of crude fusion proteins, they can also lead to heterogeneous activity of the enzymes after activation (Zhao et al, 2021; Zhao et al, 2022). Secretory expression in insect cells could produce about 20 mg/L of VyPAL2, but this approach is limited by relatively high costs.…”
Section: Introductionmentioning
confidence: 99%